Invisible Belfast: Flat ontologies and remediation of the post-conflict city - Barrios-O’Neill, Danielle and Hook, Alan (Convergence: The International Journal of Research into New Media Technologies, 2021)
[in]visible belfast was a research-driven indie alternate reality game (ARG) that ran for 6 weeks during the spring of 2011 in Belfast and was subsequently adapted, 5 years later into a fictional documentary for BBC Radio 4. The ARG is a participatory and dispersed narrative, which the audience play through. The text expands outward across both physical and digital platforms to create a mystery for the players using everyday platforms. The ARG is a product of media convergence and at its heart transmedial, defined by its complexity and modes of participation. The fictional radio documentary which remediated the ARG into a more simple linear structure, but possibly a more complex narrative form, retells parts of the story for new audiences. The premise of [in]visible belfast – the game and later the documentary – is itself an adaptation of writer Ciaran Carson’s novel The Star Factory (1997): a postmodern adventure through the complex psychogeography of Belfast. A trail through the labyrinthine text, which paints the history of Belfast in poetic prose. This article will map the concept’s journey from novel to game to radio, contextualising its development within its political and urban landscape and charting the remediation of the narratives as they fold out across multiple media and complex story arches. The article will draw together ideas from previous publications on ARG, transmediality and complex textualities from the authors and reflect on the textual trajectories that the remediation of the narrative has taken from the original book, through the ARG, into the radio documentary. Building upon recent approaches from environmental philosopher Tim Morton and games theorist Ian Bogost, the authors argue that Belfast’s history propels medial adaptations of a particular kind, characterised by a ‘flat’ ontology of space and time and a sort of diffuse and dark urban experience for designers/producers and players/listeners.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xMzU0ODU2NTE5ODk2MTc0